2017
DOI: 10.1002/lary.26555
|View full text |Cite
|
Sign up to set email alerts
|

Superior turbinate eosinophilia correlates with olfactory deficit in chronic rhinosinusitis patients

Abstract: Objective To evaluate if molecular markers of eosinophilia in olfactory enriched mucosa are associated with olfactory dysfunction. Study Design Cross-sectional study of tissue biopsies from 99 patients, and a further 30 patients who underwent prospective olfactory testing prior to sinonasal procedures. Methods Tissue biopsies were processed for analysis of inflammatory markers using qRT-PCR. Ipsilateral olfactory performance was assessed using the Sniffin Sticks threshold component and the UPSIT and age-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
67
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…Although the inflammation seen in OC histopathology usually mirrored that seen in the sinus mucosa proper, OC inflammation was not seen in all patients with CRS. Additional studies have demonstrated similar histopathologic changes in the OC of patients with CRS, with several recent studies highlighting the potential impact of local eosinophilia …”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Although the inflammation seen in OC histopathology usually mirrored that seen in the sinus mucosa proper, OC inflammation was not seen in all patients with CRS. Additional studies have demonstrated similar histopathologic changes in the OC of patients with CRS, with several recent studies highlighting the potential impact of local eosinophilia …”
mentioning
confidence: 80%
“…The most important limitation is the difficulty performing an olfactory biopsy. A number of studies described techniques to harvest OC mucosa, some in the clinic setting, but none indicated widespread adoption . Furthermore, these biopsies, by necessity, sample a focal region of the OC cleft on a single side.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…913 It is additionally recognized that the presence of NP and eosinophilia at the time of sinus surgery are also associated with increased rates of postsurgical medication use, recurrence, and revision sinus surgery. 1420 Thus, accurately identifying patients at risk for recurrence is important for tailoring individualized treatment plans.…”
mentioning
confidence: 99%